Recurrent Chronic Subdural Hematoma After Burr-Hole Surgery and Postoperative Drainage: A Systematic Review and Meta-Analysis - Lodewijkx, Roger; Foppen, Merijn; Slot, Kari-Anne Mariam; Vandertop, William Peter; Verbaan, Dagmar (Operative neurosurgery (Hagerstown, Md.), 2023)
Reported recurrence rates of chronic subdural hematoma treated by burr-hole surgery with postoperative drainage vary considerably in the literature. We performed a systematic review and meta-analysis to define the recurrence rate of burr-hole surgery with postoperative drainage. PubMed and EMBASE were searched, and Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed. We used the Newcastle-Ottawa scale and Cochrane risk-of-bias tool for quality assessment of included studies and the random-effects model to calculate pooled incidence rates in R with the metaprop function if appropriate. The search yielded 2969 references; 709 were screened full text, and 189 met the inclusion criteria. In 174 studies (34 393 patients), the number of recurrences was reported as per patient and 15 studies (3078 hematomas) reported the number of recurrences per hematoma, for a pooled incidence of 11.2% (95% CI: 10.3-12.1; I 2 = 87.7%) and 11.0% (95% CI: 8.6-13.4; I 2 = 78.0%), respectively. The pooled incidence of 48 studies (15 298 patients) with the highest quality was 12.8% (95% CI 11.4-14.2; I 2 = 86.1%). Treatment-related mortality (56 patients) has a pooled incidence of 0.7% (95% CI 0.0-1.4; I 2 = 0.0%). The recurrence rate of chronic subdural hematoma treated by burr-hole surgery and postoperative drainage is 12.8%.